The Interplay of Pedagogical Competence, Digital Literacy, and Learning Facilities in Enhancing Learning Quality: A Correlational Study in Indonesian High Schools - Satiri, Satiri; Hanafi, M. Syadeli; Muhyidin, Asep (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
Learning quality is crucial for improving the overall quality of education in Indonesia. This study aims to to analyze the relationship between pedagogical competence, digital literacy, and the utilization of learning facilities and learning quality in public senior high schools (SMA Negeri) in Serang Regency, Banten. A quantitative research approach was employed using Spearman correlation analysis on data collected from 294 respondents through random sampling across various public senior high schools in Serang Regency. Data were gathered through questionnaires, then analyzed using statistical methods (SPSS), data presentation, and conclusion drawing. The findings indicate that pedagogical competence, teachers’ digital literacy, and the utilization of learning facilities contribute to improving learning quality. The relationship between Teachers’ teacher competences (X1) and Learning Quality (Y) is 0.552. Teachers’ Digital Literacy (X2) has a correlation value of 0.527, and Utilization of Learning Facilities (X3) has a correlation value of 0.460. The multiple correlation value (Rₛ) is 0.652, with a coefficient of determination (Rₛ²) of 0.425. The calculated F-value (Fcalculate) of 71.64 is greater than the F-table value (Ftable) of 2.63 at a significance level of 0.05. The implications of this research highlight that the success of enhancing learning quality in public senior high schools in Serang Regency depends not only on curriculum policy but also on teachers’ commitment to improving their teaching quality through enhanced competence, digital literacy skills, and consistent use of learning facilities. The novelty in this research is relevance to 21st century challenges, Focused on Indonesian public high schools, emphasis on teachers’ digital literacy, measurement of learning facility utilization, and non-parametric approach with Large-Scale Likert Data. The contribution of this research is learning quality as a synergy of pedagogy, literacy, and facility use, expands quantitative non-parametric educational research, practical: supports teacher training in digital-based teaching, guides local governments to enhance learning through digital literacy and school facility optimization.